Double burden of malnutrition among women and children in Zimbabwe: a pooled logistic regression and Oaxaca-Blinder decomposition analysis - Akim Tafadzwa Lukwa; Plaxcedes Chiwire; Plaxcedes Chiwire; Folahanmi Tomiwa Akinsolu; Denis Okova; Charles Hongoro; Charles Hongoro (Frontiers Media S.A., 2024)
BackgroundThe double burden of malnutrition (DBM) is a public health issue characterised by the coexistence of undernutrition and overnutrition within the same population, household, or individual. Undernutrition, manifesting as stunting, wasting, or being underweight, results from insufficient nutrient intake while overnutrition, manifesting as overweight or obesity, results from excessive caloric intake, poor diet quality, and sedentary lifestyles. This dual burden poses significant challenges for health systems due to lost productivity and increased healthcare expenditure.MethodsThis study utilised data from the Demographic and Health Surveys (DHS) conducted in Zimbabwe for 2010-2011 and 2015, which provided information on women's and children's health and nutritional status, household characteristics, and socio-economic status. Pooled logistic regression was used to analyse the association between various sociodemographic factors and DBM among women and children. The Oaxaca-Blinder decomposition method explored differences in DBM between 2010-2011 and 2015.ResultsThe average age of mothers was approximately 31 years, and children's ages averaged around 32 months. From 2010 to 2015, there was a notable socio-economic improvement, with a decrease in the percentage of mothers in the poorest quartile from 20 to 16% and an increase in the richest quartile from 22 to 23%. The study found a slight decrease in overall household DBM among women from 34% in 2010 to 32% in 2015, while DBM among children increased from 12 to 14%. Pooled logistic regression analysis indicated that children in rural areas had statistically significantly higher odds of experiencing DBM than their urban counterparts. The Oaxaca-Blinder decomposition showed that changes in residence status significantly impacted the increase in DBM among children. At the same time, the coefficient effect accounted for most of the unexplained differences in DBM among women.ConclusionThe growing DBM among women and children in Zimbabwe is significantly influenced by changes in residence status. The findings highlight the need for targeted public health interventions to address urban-rural disparities and emphasise the importance of considering socio-economic, environmental, and behavioural factors. Context-specific public health strategies, aligned with WHO's Double Duty Actions, are essential to improve the nutritional health of Zimbabwe's population.